1997
DOI: 10.1038/sj.hdy.6881240
|View full text |Cite
|
Sign up to set email alerts
|

P-element inserts in transgenic flies: a cautionary tale

Abstract: The fruitfly, Drosophila melanogaster, can be transfected with P-elements and induced to overexpress a transfected gene whose impact on lifespan can be measured. Here, it is reported that in previous experiments a transfected gene was not expressed. This suggested a new statistical analysis indicating that (1) the size of the insert, the position and the interactions of the insert with the genetic backgrounds into which the P-element are inserted have effects on lifespan similar to those attributed to overexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…However, the ability of a particular insert of the Cu/ZnSOD overexpression construct to extend the life span was found to be affected by the genetic background. It is likely that the different responses are due to the different genomic locations of the inserts, which could affect the exact level and/or tissue distribution of enzyme overexpression and which can affect the life span (20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the ability of a particular insert of the Cu/ZnSOD overexpression construct to extend the life span was found to be affected by the genetic background. It is likely that the different responses are due to the different genomic locations of the inserts, which could affect the exact level and/or tissue distribution of enzyme overexpression and which can affect the life span (20).…”
Section: Discussionmentioning
confidence: 99%
“…Differences in genetic background of this type have been found to have effects on the life span which are large enough to mask any effects of the transgene(s) under study (20,50,51,54). Another limitation of current transgenic technologies is that overexpression occurs throughout the life cycle, and thus it is not possible to separate effects on development from effects on adult aging.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The initial reports of the extension of Drosophila life-span by the insertion of transgenes coding for superoxide dismutase (Sod) plus catalase did not survive close scrutiny (Kaiser et al 1996;Tower 1996). However, more recent work has shown that it is sucient just to increase the Cu/Zn-Sod levels in adult炉ies (Sun and Tower 1999) or to express human Cu/Zn-Sod in their motorneurons (Parkes et al 1998) in order to extend the life span of Drosophila.…”
Section: Introductionmentioning
confidence: 97%
“…One of these studies concluded that coincident over-expression of Cu/ZnSOD and catalase might be required to observe life span increase (Orr and Sohal 1994). However, several authors reviewing these results concluded the studies lacked sufficient controls for genetic background effects on life span, and this masked any possible effects of the transgenes (Tower 1996;Kaiser et al 1997;Tatar 1999). Subsequent studies using a larger number of lines confirmed that over-expression of the Cu/ZnSOD, MnSOD and catalase genes using their native promoters does not increase life span, regardless of whether the transgenes are co-over-expressed, or whether they are expressed in short-lived starting strains (Mockett et al 1999;Orr et al 2003).…”
Section: Enhanced Sod Function and Agingmentioning
confidence: 93%